2023
DOI: 10.1186/s12891-023-06154-x
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of Kinesio taping combined with cervical muscles multi-angle isometric training in patients with cervical spondylosis

Abstract: Objective The purpose of this study was to investigate the efficacy of Kinesio taping (KT) combined with multi-angle isometric resistance training for cervical spondylosis. Methods Sixty-one patients were divided into two groups by random number table method. Both groups were given multi-angle isometric training, the patients in the observation group were supplemented with Kinesio taping. Before and after treatment, the symptoms of cervical spine f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Unfortunately, the dependence on electronic devices seems to be gradually having a negative impact on people's health. It has been reported that there has been a worldwide increase in the number of people diagnosed with cervical spine disorders associated with prolonged use of electronic devices such as mobile phones, [ 1,2 ] moreover, it is also common for adolescents to suffer from cervical spondylosis, [ 3 ] which should be taken seriously and addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the dependence on electronic devices seems to be gradually having a negative impact on people's health. It has been reported that there has been a worldwide increase in the number of people diagnosed with cervical spine disorders associated with prolonged use of electronic devices such as mobile phones, [ 1,2 ] moreover, it is also common for adolescents to suffer from cervical spondylosis, [ 3 ] which should be taken seriously and addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding strategies for preserving and improving ACROM, multiple approaches can be considered, such as reducing screen time, minimizing sedentary behavior, receiving massages, engaging in targeted exercises, utilizing cupping techniques, and employing elastic taping [23][24][25][26][27]. Among these solutions, elastic taping (ET) possesses a distinctive characteristic: it can be worn directly on the skin for an extended period, continuously working 24 h a day and adapting to the subject's movements until its removal.…”
Section: Introductionmentioning
confidence: 99%
“…Turning to strategies for preserving and improving ACROM, multiple approaches can be considered, such as reducing screen time, minimizing sedentary behavior, receiving massages, engaging in targeted exercises, utilizing cupping techniques, and employing elastic taping [23][24][25][26][27]. Among these solutions, elastic taping (ET) possesses a distinctive characteristic: it can be worn directly on the skin for an extended period, continuously working 24 hours a day and adapting to the subject's movements until removal.…”
Section: Introductionmentioning
confidence: 99%